Oxaliplatin induces muscle loss and muscle‐specific molecular changes in Mice. Issue 4 (6th October 2017) - Feather, Claire E.; Lees, Justin G.; Makker, Preet G.S.; Goldstein, David; Kwok, John B.; Moalem‐Taylor, Gila; Polly, Patsie
ABSTRACT: Introduction: Muscle wasting is a frequent, debilitating complication of cancer. The impact of colorectal cancer chemotherapeutic oxaliplatin on the development of muscle loss and associated molecular changes is of clinical importance. Methods: C57BL/6J male mice were treated with oxaliplatin. Total body weights were measured and behavioral studies performed. Hindlimb muscle weights (gastrocnemius and soleus) were recorded in conjunction with gene and protein expression analysis. Results: Oxaliplatin‐treated mice displayed reduced weight gain and behavioral deficits. Mice treated over a shorter course had significantly increased STAT3 phosphorylation in gastrocnemius muscles. Mice receiving extended oxaliplatin treatment demonstrated reduced hindlimb muscle mass with upregulation of myopathy‐associated genes Foxo3, MAFbx, and Bnip3 . Discussion: The findings suggest that oxaliplatin treatment can directly disrupt skeletal muscle homeostasis and promote muscle loss, which may be clinically relevant in the context of targeting fatigue and weakness in cancer patients. Muscle Nerve 57 : 650–658, 2018